The accumulation of muscle RING finger-1 in regenerating myofibers: Implications for muscle repair in immune-mediated necrotizing myopathy - Yang, Meng-Ge; Zhang, Qing; Wang, Hong; Ma, Xue; Ji, Suqiong; Li, Yue; Xu, Li; Bi, Zhuajin; Bu, Bitao (Frontiers in Neurology, 2022)
Background Muscle RING finger-1 (MuRF-1) plays a key role in the degradation of skeletal muscle proteins. We hypothesize the involvement of MuRF-1 in immune-mediated necrotizing myopathy (IMNM). Methods Muscle biopsies from patients with IMNM (n = 37) were analyzed and compared to biopsies from patients with dermatomyositis (DM, n = 13), dysferlinopathy (n = 9) and controls (n = 7) using immunostaining. Results MuRF-1 staining could be observed in IMNM, DM and dysferlinopathy biopsies, whereas the percentage of MuRF-1 positive myofibers was significantly higher in IMNM than in dysferlinopathy (p = 0.0448), and positively correlated with muscle weakness and disease activity in IMNM and DM. Surprisingly, MuRF-1 staining predominantly presented in regenerating fibers but not in atrophic fibers. Moreover, MuRF-1-positive fibers tended to be distributed around necrotic myofibers and myofibers with sarcolemma membrane attack complex deposition. Abundant MuRF-1 expression in IMNM and DM was associated with rapid activation of myogenesis after muscle injury, whereas relatively low expression of MuRF-1 in dysferlinopathy may be attributed to damaged muscle regeneration. Conclusions MuRF-1 accumulated in regenerating myofibers, which may contribute to muscle injury repair in IMNM and DM. MuRF-1 staining may help clinicians differentiate IMNM and dysferlinopathy.